Applicability of Financial Inclusion in the University of Zakho - Jabar, Dilshad; Sultan, Hikmat (Humanities Journal of University of Zakho, 2023)
The study aims to clarify the availability of financial inclusion among the academic staff at the University of Zakho, as well as the possibility of applying the philosophy of financial inclusion in an electronic manner and the extent of its importance for the academic staff in carrying out their activities, whether in purchasing resources or publishing research in international scientific journals, Additionally this study intend to identify the rates of financial inclusion in the sample surveyed and the most important determining’s facing others in not adopting this concept. The study relied on the descriptive analytical approach to measure and complete its requirements, depending on the questionnaire as a main tool for collecting data, which numbered (78) and were analyzed through statistical programs (SPSS. Ver-25). The researchers reached a number of conclusions, the most important of which is that the quality of financial services occupies the first place of the respondents' interest in financial inclusion, while the use of financial services and its technologies is the last of their concerns. The researchers presented a set of Recommendations, the most important of which was to improve the quality of banking services to attract as many customers as possible and provide techniques to facilitate the task of obtaining financial service easily, quickly and safely.